Ethical Guidelines for the Use of AI In Hadith Studies - Mesbahul Hoque; A. Irwan Santeri Doll Kawaid; Shumsudin Yabi (Fakulti Pengajian Quran dan Sunnah, 2025)
E-Proceeding The9th International Conference on Nabawi Heritage(SWAN 2024) Theme: Prophetic Legacy in Development of Civil Society in the Era of Artificial Intelligence (AI) 6-7 November 2024